The ocean-atmospheric condition around Pieh Islands – Western Sumatra, Indonesia and its role on coral reef resilience. (November 2018) - Corvianawatie, C; Abrar, M; Wouthuyzen, S; Darmawan,; Kusumo, S; Samsuardi,; Yennafri,; Salatalohi, A; Hanif, A; Permana, S; Arrafat, M Y; Tanto, T A
Abstract: Pieh Islands located at the Western Sumatra is one of the most affected areas by massive coral bleaching during 2015-2016. The persistence warming or cooling of sea surface temperature due to regional climate phenomena such as El Niño Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) put the coral reef into stress condition leading into coral bleaching. However, corals have an ability to recover from such bleaching condition into normal state by reducing its stressors. A suitable oceanographic condition such as normal range of temperature and salinity, low nutrient concentration, and low sedimentation rate could support corals recovery process. This study aims to understand the variability of the ocean and atmospheric data and its role in coral reef recovery. Data gained from in situ measurements of water quality at Pieh Marine Conservation Area (PMCA) on June 2018. Several historical ocean-atmospheric data were collected to analyze their temporal variability. It is confirmed that the bleaching event was caused by positive IOD and El Niño condition in 2015-2016. However, there is the sign of coral reef recovery during 2017-2018 which is suggested due to the relatively normal condition of the ocean and atmospheric parameters in Pieh Islands.